Family farming and gendered division of labour on the move: a typology of farming family configurations - Contzen, Sandra; Forney, Jérémie (My University, 2017)
Family farming, understood as a household which combines family, farm and commercial activity, still represents the backbone of the world’s agriculture. On family farms, labour division has generally been based on complementarity between persons of different gender and generations, resulting in specific male and female spheres and tasks. In this ‘traditional’ labour division, gender inequality is inherent as women are the unpaid and invisible labour force. Although this ‘traditional’ labour division still prevails through time and space, new arrangements have emerged. This paper asks whether we are witnessing changes in the unequal structure of family farming and analyses the diversity of farming family configurations, using the Swiss context as a case study. The typology of farming-family configurations developed, based on qualitative data, indicates that inequalities are related to status on the farm and position in the configuration rather than to gender identity per se. This insight enables a discussion of equality and fairness in a new light. This paper shows that farming-family configurations are often pragmatic but objectively unequal. However, these arrangements might still be perceived as fair when mutual recognition exists, resulting in satisfaction among the family members. The paper concludes that although family farming presents challenges to gender equality, some types of farming-family configurations offer new pathways towards enhanced gender equality.
Keywords: Gender equality Family farming Switzerland Farming-family configuration